A Comparision Of The Impact Of Local, State, And Federal Taxes In Eight U.S. States - Robert L. Davidoff (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
INTRODUCTION The impact of taxation differs substantially from state to state in a complex fashion that depends on both the physical characteristics of a mineral deposit and on the price of the mineral commodity relative to its costs of production. A comparative analysis of the tax structures of eight states (Arizona, Colorado, Idaho, Montana, Nevada, New Mexico, Utah and Wisconsin) showed wide variations in rates of return for any given type of mineral property, with no state having either the most burdensome or least burdensome tax structure under all circumstances. Three hypothetical mineral operations were analyzed: a producing open-pit copper property, a non-producing underground platinum operation, and a non-producing underground gold operation. None of them corresponds exactly to an existing property. Each of these property types is further defined to have ore feed grades at three different levels, leading to three potential profitability levels, referred to in this paper as "economic", "marginal" and "subeconomic". Thus the differential impact of state tax structures is measured for mineral properties of different types, as well as for different profitability levels. Montana is used as the base case. This study does not address the topic of corporate structures or tax consolidation. There are no costs assumed external to the operation of the deposit (e.g. exploration to locate additional deposits). Two types of analyses were performed for this study. The first calculates the total cumulative tax payments in each state using all applicable taxes (including U.S. federal income taxes and examines the resultant differences in discounted cash-flows rate of returns DCFROR's amoung the eight states. The second is a sensitivity analysis that examines each type of state tax separately (i.e. state income, property, and severance taxes) in order to isolate and examine the differences in tax payments that are due to the difference in rates and methods of computing specific types of taxes in each state. The results of this study serve to illustrate the complex nature of interactions among various taxes. For example, property tax is a deduction in calculating severance tax in some state. Changes in property-tax and severance-tax payments both enter into the calculation of state and federal income-tax liability. This, in turn, could change the timing and usage of tax-loss carry forward amounts and investment tax credits. Additionally, the physical characteristics of a property, the method and costs at which the mineral will be extracted, and the profitability level at which each property operates will affect tax treatment. Each mineral operation was evaluated at three different predetermined profitability levels, referred to using the terms economic, marginal and sub-economic. These three profitability levels are defined by the ore feed grades of the primary commodity that yield in constant terms, approximately an "economic" 18% DCFROR, "a marginal." 10% DCFROR, and a "sub-economic" 5% DCFROR, respectively, under the Montana tax structure. In the analyses, the mining and processing parameters for each of the three types of properties were assumed to be identical for each of the eight states. It was assumed that each operation produces at full operating capacity throughout its life. This implies the level of mineral commodity demand will support the inferred commodity price, such that each operation will be able to sell all its output. The analyses performed for this study were done using a comprehensive economic evaluation simulator that is used in the Bureau of Mines, Division of Minerals Availability MAS program to perform DCFROR analyses. All economic evaluations performed upon these data (see appendix 2) were in constant January 1981 dollars. By-product prices used for the analyses were: [Gold $425.00/troy ounce Palladium$200.00/troy ounce Silver $ 10.00/troy ounce] Typical cash-flow calculation layout is given in Appendix 3. The initial step for each evaluation is to define an "economic" profitability level scenario. An 18% DCFROR rate in Montana was considered the